A transporter’s doom or destiny: SLC6A1 in health and disease, novel molecular targets and emerging therapeutic prospects - Shah, Nikita; Kasture, Ameya S.; Fischer, Florian P.; Sitte, Harald H.; Hummel, Thomas; Sucic, Sonja (Frontiers in Molecular Neuroscience, 2024)
As the first member of the solute carrier 6 (SLC6) protein family, the γ-aminobutyric acid (GABA) transporter 1 (GAT1, SLC6A1), plays a pivotal role in the uptake of GABA from the synaptic cleft into neurons and astrocytes. This process facilitates the subsequent storage of GABA in presynaptic vesicles. The human SLC6A1 gene is highly susceptible to missense mutations, leading to severe clinical outcomes, such as epilepsy, in the afflicted patients. The molecular mechanisms of SLC6A1-associated disorders are discerned to some degree; many SLC6A1 mutations are now known to impair protein folding, and consequently fail to reach the plasma membrane. Inherently, once inside the endoplasmic reticulum (ER), GAT1 abides by a complex cascade of events that enable efficient intracellular trafficking. This involves association with specialized molecular chaperones responsible for steering the protein folding process, oligomerization, sorting through the Golgi apparatus, and ultimately delivery to the cell surface. The entire process is subject to stringent quality control mechanisms at multiple checkpoints. While the majority of the existing loss-of-function SLC6A1 variants interfere with folding and membrane targeting, certain mutants retain abundant surface expression. In either scenario, suppressed GAT1 activity disrupts GABAergic neurotransmission, preceding the disease manifestation in individuals harboring these mutations. The nervous system is enthralling and calls for systematic, groundbreaking research efforts to dissect the precise molecular factors associated with the onset of complex neurological disorders, and uncover additional non-canonical therapeutic targets. Recent research has given hope for some of the misfolded SLC6A1 variants, which can be salvaged by small molecules, i.e., chemical and pharmacological chaperones, acting on multiple upstream targets in the secretory pathway. We here highlight the significance of pharmacochaperoning as a therapeutic strategy for the treatment of SLC6A1-related disorders.